2015
DOI: 10.1590/s0100-736x2015000400009
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characterization of Campylobacter spp.isolates in dogs, cats and children

Abstract: RESUMO.-[Ocorrência e caracterização de isolados de Campylobacter spp. em cães, gatos e crianças.] Com o objetivo de melhorar o entendimento das infecções porCampylobacter spp. em cães, gatos e crianças no Brasil, foram avaliadas 160 amostras fecais de crianças e 120 swabs retais de pets (103 cães e 17 gatos). Do total das amostras das crianças, 6,87% foram positivas para Campylobacter spp. e em cães e gatos a positividade foi de 18,3%. Das 33 amostras positivas para Campylobacter spp., 57,6% foram identificad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
2
13
1
1
Order By: Relevance
“…The other studies reported Campylobacter infection rates of 4.81-51.1%. 5,[22][23][24][25][26][27] The variation in the rate of infection may rely on the sample size, age, diet, and gastrointestinal status (diarrheal or healthy) of the studied dogs, different diagnosis methods, and geographical location, as well as the season of sampling. The most prevalent species of Campylobacter among the dogs were C. coli (38.89%) and C. jejuni (33.33%).…”
Section: Discussionmentioning
confidence: 99%
“…The other studies reported Campylobacter infection rates of 4.81-51.1%. 5,[22][23][24][25][26][27] The variation in the rate of infection may rely on the sample size, age, diet, and gastrointestinal status (diarrheal or healthy) of the studied dogs, different diagnosis methods, and geographical location, as well as the season of sampling. The most prevalent species of Campylobacter among the dogs were C. coli (38.89%) and C. jejuni (33.33%).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a high percentage of the cadF , flaA genes and iam sequence in both groups of dogs. Rodrigues et al [ 33 ] observed a high incidence of the cadF and flaA genes in dogs and noted that these genes may act as reporters in research on the mechanisms of C. jejuni pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CJ multidrug resistance to different antibiotics used in poultry and humans has been currently noticed. It was described that children and pets with CJ infections were resistant to ceftiofur, sulphazotrim, norfloxacin, tetracycline, amoxicillin, ciprofloxacin, cefazolin, and erythromycin antibiotics ( Rodrigues et al., 2015 ). Furthermore, another work showed that CJ isolated from chicken carcasses were highly resistant to norfloxacin, erythromycin, and amoxicillin, the most used drugs in traditional antibiotic therapy ( Fonseca et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%